Respuesta :

122095

Answer:

x=−3+√14 or x=−3−√14

Answer: Bottom of explanation

Step-by-step explanation:

We need to get zero on one side so we can perform the quadratic formula on these. When we make the equation  0=x^2+6x-5, a=1, b=6, and c=-5. With our newfound knowledge, we can perform the quadratic formula,

-b+/-√b^2-4ac/2a

plugging in these numbers, we get two solutions through:

[tex]\frac{-6+\sqrt{36^2-4(1*-5)}}{2*1}[/tex]

[tex]\frac{-6-\sqrt{36^2-4(1*-5)}}{2*1}[/tex]

Solutions:

[tex]x_{1}=[/tex] [tex]-3+\sqrt{329}[/tex]

[tex]x_{2}=[/tex] [tex]-3-\sqrt{329}[/tex]